2012
DOI: 10.1089/jwh.2012.3708
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intimate Partner Violence and Childhood Sexual Abuse with Cancer-Related Well-Being in Women

Abstract: Background: Limited evidence suggests that intimate partner violence (IPV) may be associated with poorer cancer outcomes. We hypothesized that timing and type of IPV as well as childhood sexual abuse (CSA) may negatively affect depression, perceived stress, and cancer-related well-being. Methods: This was a cross-sectional study of women diagnosed with either breast, cervical, or colorectal cancer in the prior 12 months included in the Kentucky Cancer Registry. Consenting women were interviewed by phone (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
3
33
3
Order By: Relevance
“…When comparing the level of violence found in this study (35.08%) in the present study, lower levels were found by Modesitt et al [12] and Coker et al [36] where the rate of women with breast cancer and who have suffered some form of violence during life was 22.44% and 36%, respectively. However, as it was seen in these studies [12,36], it is not possible to make comparisons and concrete statements about violence being a factor to the diagnosis of breast cancer.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…When comparing the level of violence found in this study (35.08%) in the present study, lower levels were found by Modesitt et al [12] and Coker et al [36] where the rate of women with breast cancer and who have suffered some form of violence during life was 22.44% and 36%, respectively. However, as it was seen in these studies [12,36], it is not possible to make comparisons and concrete statements about violence being a factor to the diagnosis of breast cancer.…”
Section: Discussioncontrasting
confidence: 55%
“…However, as it was seen in these studies [12,36], it is not possible to make comparisons and concrete statements about violence being a factor to the diagnosis of breast cancer. However, we can say that violence brings physical, mental and emotional consequences for the lives of these women, causing the emotional and psychological factor to be affected in such a way that ends up increasing stress factors.…”
Section: Discussionmentioning
confidence: 91%
“…Intimate partner violence (IPV) has mental [1] and physical [2] health effects yet little research has investigated the impact of IPV on cancer-related quality of life (QOL) during cancer treatment and recovery [3, 4]. As defined by the Centers for Disease Control and Prevention, intimate partner violence (IPV) includes physical violence, sexual violence, stalking and psychological aggression (including coercive acts) by a current or former intimate partner [5].…”
Section: Introductionmentioning
confidence: 99%
“…IPV has consistently been associated with increased self-perceived stress including symptoms of post-traumatic stress disorder (PTSD) among women with [4] and without cancer [8]. Convincing epidemiologic and clinical evidence now links chronic stress, depression and cancer progression [9–11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation